2020
DOI: 10.1136/ijgc-2020-001656
|View full text |Cite
|
Sign up to set email alerts
|

Clear cell carcinoma of the ovary: a clinical and molecular perspective

Abstract: Clear cell carcinoma of the ovary has distinct biology and clinical behavior. There are significant geographical and racial differences in the incidence of clear cell carcinoma compared with other epithelial ovarian tumors. Patients with clear cell carcinoma are younger, tend to present at an early stage, and their tumors are commonly associated with endometriosis, which is widely accepted as a direct precursor of clear cell carcinoma and has been identified pathologically in approximately 50% of clear cell ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
107
1
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(114 citation statements)
references
References 128 publications
2
107
1
4
Order By: Relevance
“…In another report, loss of ARID1A expression was more frequent in CCC cases with (54%) than in those without (30%) PI3K/AKT pathway activation ( p = 0.046) [ 25 ]. Several genomic studies based on next-generation sequencing data have demonstrated that ARID1A and PIK3CA mutations frequently coexist in both CCC (20–56%) [ 29 ] and EC (11–25%) [ 21 , 22 ]. In addition, Mabuchi et al conducted proteome analysis of 98 primary ovarian tumors (52 CCCs and 46 HGSCs) using a tissue microarray and showed that AKT, mTORC1, and mTORC2 are more frequently activated in the former than in the latter [ 30 ].…”
Section: Genomic Profiling Of Endometriosis-associated Ovarian Canmentioning
confidence: 99%
“…In another report, loss of ARID1A expression was more frequent in CCC cases with (54%) than in those without (30%) PI3K/AKT pathway activation ( p = 0.046) [ 25 ]. Several genomic studies based on next-generation sequencing data have demonstrated that ARID1A and PIK3CA mutations frequently coexist in both CCC (20–56%) [ 29 ] and EC (11–25%) [ 21 , 22 ]. In addition, Mabuchi et al conducted proteome analysis of 98 primary ovarian tumors (52 CCCs and 46 HGSCs) using a tissue microarray and showed that AKT, mTORC1, and mTORC2 are more frequently activated in the former than in the latter [ 30 ].…”
Section: Genomic Profiling Of Endometriosis-associated Ovarian Canmentioning
confidence: 99%
“…These are chemoresistant tumors with a poor prognosis if diagnosed at an advanced stage, but most of these cases are diagnosed early with a good prognosis [83]. They are a distinct class of EOCs thought to arise from endometriosis or clear cell adenofibroma, hence they are associated with endometriosis which is thought to be the precursor for CCC manifestation and this association is considered a good prognosis [85]. Late menopause and endometriosis are considered to be the highest risk factors for developing CCCs.…”
Section: Clear-cell Carcinomasmentioning
confidence: 99%
“…The most common genomic alterations identified in CCCs are activating mutations in PIK3CA, a regulator of the PI3K-PTEN-AKT pathway (50%), and loss of function in ARID1A, component of SWI/SNF chromatin remodeling complex (50%) [86]. Other mutations reported in varying degrees are MET gene amplification, mutations in ARID1B, SMARCA4, ERBB2, PIK3CA, PIK3R1, AKT2, PTEN, KRAS, PPP2R1A, TP53, TERT promoter, and ZNF217 overexpression [85,87]. Antioxidant genes like Glutathione peroxidase 3 (GPX3), glutaredoxin (GLRX), and superoxide dismutase 2 (SOD2) are reported to be highly expressed in CCCs rendering them resistant to chemotherapy [88].…”
Section: Clear-cell Carcinomasmentioning
confidence: 99%
“…Previous studies have shown that OCCC is relatively less aggressive in the early stage 2 but may develop chemo-resistance in the advanced stage, leading to a significantly poorer prognosis compared with high-grade serous ovarian cancer. 3 , 4 …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that OCCC is relatively less aggressive in the early stage 2 but may develop chemo-resistance in the advanced stage, leading to a significantly poorer prognosis compared with high-grade serous ovarian cancer. 3,4 With developments in minimally invasive techniques, especially the wide use of laparoscopy, more gynecologic oncologists are considering minimally invasive surgery (MIS) in select patients. 5 MIS was first applied to assess tumor burden and to evaluate the resectability of advancedstage ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%